Evaluation of knowledge and practice behaviors of a group of Iranian obstetricians, general practitioners, and midwives, regarding periodontal disease and its effect on the pregnancy outcome - Ali Golkari; Hengameh Khosropanah; Faezeh Saadati (Journal of Public Health Research, 2013)
Background. Periodontal disease is considered as a risk factor for poor pregnancy outcomes, including preterm birth and low birth weight. Only few studies have assessed the knowledge and practice behaviours of healthcare providers, concerning oral health during pregnancy, periodontal diseases and their role in adverse pregnancy outcomes. The present study aimed to compare the knowledge and practice behaviours of a group of Iranian obstetricians, general practitioners, and midwives about periodontal disease. Design and methods. A cross-sectional study was conducted using a self-administered, structured questionnaire that was previously used in North Carolina. The questionnaire was translated into Persian language and was randomly distributed among 200 obstetricians, general practitioners, and midwives participating in an international congress. Data were analysed by Chi-square and spearman correlation tests using SPSS statistical software (version PASW 18). Results. A total of 150 completed the questionnaires, achieving a response rate of 75%. Totally, the knowledge of the obstetricians was more accurate compared to the two other groups and the midwives were the worst. More experienced general practitioners (P=0.002) and obstetricians (P=0.049) did less dental examinations for their patients during their first visit or periodically. More experienced obstetricians also referred their patients for dental examinations during pregnancy less than their less experienced colleagues (P<0.001). Conclusions. Although the participants had some knowledge about periodontal disease and its association with adverse pregnancy outcomes, there is much space for improvements. The participants’ attitude and knowledge were consistent.